Optimal treatment for post-MI heart failure in rats: dapagliflozin first, adding sacubitril-valsartan 2 weeks later - Tao, Wenqi; Yang, Xiaoyu; Zhang, Qing; Bi, Shuli; Yao, Zhuhua (Frontiers in Cardiovascular Medicine, 2023)
Background: Dapagliflozin (DAPA) and sacubitril-valsartan(S/V) can improve the prognosis of patients with heart failure (HF). We tested whether early initiation of SGLT2i, or different orders of combination with S/V wouldresult in a greater improvement of heart function than S/V alone in post-myocardial infarction HF (post-MI HF). Methods: To observe the therapeutic effect of DAPA and/ or S/V in post-MI HF, we induced heart failure in rats via surgical ligation of the left anterior descending (LAD) coronary artery and subsequently divided rats with MI（or sham） into 6 groups: A: Sham, B: MI, C: MI + S/V(1st d), D: MI + DAPA(1st d), E: MI +S/V(1st d)+DAPA(14th d), F: MI + DAPA(1st d)+S/V(14th d ). Histology, western blot, RNA-seq analysis of gene expression etc. were employed to explore the optimal treatment to preserve the heart function in the onset of MI. Results: We found that infarct and fibrosis area, mitochondria-dependent apoptosis (Bcl2/Caspase3) and pathway related to cardiac fibrosis (TGF-β/SMAD2) were extremely higher in post-MI HF than in the control group, while these pathological injury were notably reversed by DAPA or S/V. Cardiac structure and function were also significantly improved in those two groups. The two treatment groups were similarly effective in preventing HF. Adding DAPA to the background of S/V did not improve the results further than S/V alone. The group administered with S/V followed by DAPA showed significantly improved blood pressure as well as echocardiography test results, and histology profile. Furthermore, the RNA-Seq data showed that DAPA could activate oxidative phosphorylation components in response to MI stress. Conclusions: Treatment with DAPA was comparable to that with S/V on preserving heart structure and function in MI. S/V followed by DAPA was indicated an optimum treatment plan and demonstrated a significant therapeutic effect on MI. However, on the basis of S/V, adding DAPA did not further improve cardiac function.